Musical culture in the world of Adam de la Halle
1 online resource.
Keywords: In Musical Culture in the World of Adam de la Halle , contributors from musicology, literary studies, history, and art history provide an account of the works of 13th-century composer Adam de la Halle, one of the first named authors of medieval vernacular music for whom a complete works manuscript survives. The essays illuminate Adam’s generic transformations in polyphony, drama, debate poetry, and other genres, while also emphasizing his place in a large community of trouvères active in the bustling urban environment of Arras. Exploring issues of authorship and authority, tradition and innovation, the material contexts of his works, and his influence on later generations, this book provides the most complete and up-to-date picture available in English of Adam’s œuvre . Contributors are Alain Corbellari, Mark Everist, Anna Kathryn Grau, John Haines, Anne Ibos-Augé, Daniel E. O’Sullivan, Judith A. Peraino, Isabelle Ragnard, Jennifer Saltzstein, Alison Stones, Carol Symes, and Eliza Zingesser.